A Pragmatist Approach to Complexity Theorizing in Project Studies: Orders and Levels. Issue 3 (June 2021) - Tywoniak, Stephane; Ika, Lavagnon; Bredillet, Christophe
The limitations of complexity theorizing in project studies are traced back to simplistic and reductionist theorizing strategies. This article offers pragmatist recommendations to develop strong theorizing strategies organized in a triad: orders of theorizing (degree of recursiveness of the theorizing process), levels of theorizing (interactions between micro, meso, and macro loci of analysis), and the integration between orders and levels brought together in a recursive relationship of co-construction. We offer four main contributions to complexity theorizing in project studies: pragmatism is useful, deeper attention should be paid to theorizing across levels, third-order theorizing is needed, and complexifying terminology is required.